MICROCONTROLLER BASED ROBOT PROTOTYPE MANUAL CONTROL WITH ATMEGA8535 JOYSTICK - Azella Maulidya; Luyung Dinaini, Skom, MMSi (Jurnal Sistem Komputer, 2008)
In writing that I make with the title "PROTOTYPE ROBOT WITH MANUAL CONTROLS microcontroller ATMega8535 joystick" is intended to be a control instrument to be developed further into a tool of control that can be more useful again .